Potable Water and Terrestrial Resources on Grand Bahama Post-Hurricane Dorian: Opportunities for Climate Resilience - Welsh, Kristen; Bowen-O'Connor, Clare; Stephens, Mark; Dokou, Zoi; Imig, Anne; Mackey, Tara; Moxey, Andrew; Nikolopoulos, Efthymios; Rein, Arno; Turner, Amber; Williams, Amano; Al Baghdadi, Layla; et al. (International Journal of Bahamian Studies, 2022)
The catastrophic impact of Hurricane Dorian in September 2019 was unprecedented for the island of Grand Bahama. Flooding in the western portion of the island damaged pine ecosystems, inundated the soil and groundwater with salt water, and disrupted potable water service throughout the island. More than two years post-Hurricane Dorian, the freshwater lenses that the island relies on for potable water are still inundated with salt water. This collaborative paper summarizes all efforts of researchers and practitioners to evaluate the freshwater lenses, as well as their associated ecosystems, that serve as the main source of drinking water for the island of Grand Bahama. Hydrogeologic and vegetation assessments were conducted on the two primary wellfields that provide 95% of the drinking water to the island, over the span of two and a half years from the immediate aftermath of Hurricane Dorian through present day. While salinity and total dissolved solid concentrations in groundwater have declined, present levels indicate that the full recovery of the freshwater lenses may take decades. Forest assessments indicate that in Wellfield 6, which was the primary source of potable water pre-Hurricane Dorian, the pine forests suffered significant damage with complete pine mortality and little regeneration of pine trees occurring, which could impact the underlying freshwater lens. Lessons learned from this event underscore the vulnerability of water resources in The Bahamas and the critical need for adaptation strategies to improve resilience to future extreme events and climate change.